Different development of global warming (GW) and urban heat island (UHI) in the city of Zagreb - Bonacci, Ognjen (Acta hydrotechnica, 2023)
The analysis examines various impacts of global warming (GW) and urban heat island (UHI) effects at four meteorological stations in and around Zagreb, Croatia, spanning from 1981 to 2021. The goal was to determine the intensity and causes of the different warming tendencies and behaviour of air temperature variations observed in various parts of Zagreb. Data from four meteorological stations were analysed: Grič (GR) – a hill within the city area, Maksimir (MA) – an urbanized suburban area, Pleso (PL) – a suburban area unaffected by intense urbanization (airport), and Puntijarka (PU) – atop of Mt. Medvednica. Various statistical methods were applied to analyse trends and variations in annual, monthly, and daily air temperature indices (ATI), including linear regression, the Mann–Kendall test, the day-to-day variability method (DTD), and diurnal air temperature range (DTR) method. All stations showed increasing trends in all ATI. At the PU station, the trend is solely due to GW; at others, both UHI and GW contribute. The MA station exhibits the most pronounced UHI. DTD variability decreases at all stations. GR sees an increasing DTR trend, while PU's trend is decreasing. No DTR trends were observed at the other two stations. Overall, ATI variations are similar, but each location's behaviour differs due to its unique local environment.
Keywords: air temperature trend; day-to-day air temperature variability; diurnal air temperature range; global warming; lobalno segrevanje; mestni toplotni otok; mesto Zagreb; razpon dnevne temperature zraka; spremenljivost dnevne temperature zraka; trend temperature zraka; urban heat island; Zagreb City